2012
DOI: 10.1007/978-1-4614-4989-8_29
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Red Cell Distribution Width with Red Blood Cell Deformability

Abstract: The red cell distribution width (RDW) is a component of the automated complete blood count (CBC) that quantifies heterogeneity in the size of circulating erythrocytes. Higher RDW values reflect greater variation in red blood cell (RBC) volumes and are associated with increased risk for cardiovascular disease (CVD) events. The mechanisms underlying this association are unclear, but RBC deformability might play a role. CBCs were assessed in 293 adults who were clinically examined. RBC deformability (expressed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(164 citation statements)
references
References 10 publications
4
157
2
1
Order By: Relevance
“…nutritional deficiency, and bone marrow dysfunction. Larger variation of red blood cell volume is strictly associated with decreased erythrocyte deformability, which in turn impairs blood flow through microcirculation (23). Oxidative stress was also revealed to be involved in the association between elevated RDW and clinical endpoints (24,25).…”
Section: Figurementioning
confidence: 96%
“…nutritional deficiency, and bone marrow dysfunction. Larger variation of red blood cell volume is strictly associated with decreased erythrocyte deformability, which in turn impairs blood flow through microcirculation (23). Oxidative stress was also revealed to be involved in the association between elevated RDW and clinical endpoints (24,25).…”
Section: Figurementioning
confidence: 96%
“…A potentially promising, cost-effective, and high throughput method for measuring RBC deformability is microfluidics [35][36][37][38][39][40][41]. Deformability measurements using microfluidics uses minute amounts of a whole blood or RBC suspension flowing through a funnel-shaped microconstriction [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that EPA taken up into the red blood cell membrane improves cell deformability by stabilizing the membrane. Furthermore, an increased red blood cell deformability might be associated with low RDW values 31) . Therefore, it is suggested that the reduction of cardiovascular events by the treatment with EPA may be mediated by the reduction in the RDW value via the stabilization of the red blood cell membrane.…”
Section: Discussionmentioning
confidence: 99%